The Effects Of Green Colour On Patients Under Recovering According To Noble Alquran - Yaroub S. , Ali Al Obaidi (2014)
This study focuses on the effect of green color specifically in acceleration recovering of patients under treatment in treatment centers and its impact on the psychological aspect of the treatment, in particular, which is one of the stages of complementary and important in treatment as in cases of post-surgical and other cases which have been based on this study, the green color had ever been in the noble ALQURAN many times and places and focus on how the color calls for calm and balance, growth and peace of mind as well as based on scientific studies took the green color as a main subject to study and its effects on the psychological aspect of human. This study is simple but it comes as part of what’s called now days the science of Quranic miracle which to utilize what is stated in the noble ALQURAN in all aspects of life, including scientific, legal, legislative, and life sciences, mathematics, and many other issues .This study is an approach according to our perception humble as stated in the noble ALQURAN, because the reality is out of our thinking Border and what we want to reach is access to its virtual image simple signals colorimetric contained in the noble ALQURAN, which could use them to find the determinants or guide or standard of design according to researchers, architects and specialists in find a comfortable designs and commensurate with the requirements of users.